Neighborhood context and birth outcomes: Going beyond neighborhood disadvantage, incorporating affluence. (December 2017) - Kane, Jennifer B.; Miles, Gandarvaka; Yourkavitch, Jennifer; King, Katherine
Highlights: Neighborhood affluence protects against the risk of poor birth outcome. The protective effect of affluence holds for Whites, Blacks, Hispanics and Asians. Mediation of these pathways by prenatal smoking varies by racial group. The discourse on neighborhoods and birth outcomes should include affluence.